The relationship between teacher motivation, self-efficacy and teaching reading comprehension skills: the case of ESL teachers in Hyderabad, India - Begum, Farhath Unissa (2019)
The teaching of reading comprehension skills depends on teacher motivation and self-efficacy, which is a major concern among most English as second language (ESL) teachers in many Indian schools. Many constraints, such as large classrooms, students’ attitude and insufficient infrastructure, adversely affect teacher motivation and self-efficacy. The government schools in the Telangana state reported a lack of teacher motivation and self-efficacy and a persistent decline in students’ reading skills. Accordingly, the government has imposed an eligibility test and a two-year training for teachers. However, scientific studies on teacher motivation and self-efficacy, particularly on the ESL teachers in this region, are still lacking. The present study, therefore, aims to examine the relationship between teacher motivation, self-efficacy and teaching reading comprehension skills among ESL teachers of the government secondary schools in the Hyderabad district, India. The data were collected through surveys and semi-structured interviews. The explanatory sequential approach of a mixed-methods design was employed in which the quantitative and qualitative data were integrated at the intermediate and final stages of the study. The questionnaires to measure teacher motivation, self-efficacy and teaching reading comprehension skills were adopted from Teachers’ Sense of Efficacy Scale (TSES) and Progress in International Reading Literacy Study (PIRLS). The findings indicate a positive relationship between teacher motivation, self-efficacy and teaching reading comprehension skills among the participants of the study, lending evidence that an adequately motivated and efficacious teacher can influence students’ reading achievements. The study has provided some useful information to the state’s Ministry of Education on teacher motivation, self-efficacy and teaching reading comprehension skills. The results may guide the government in their efforts towards enhancing teacher motivation and self-efficacy and ensuring quality education. It is recommended that the government should stimulate, sustain and support teachers to enhance the quality of their teaching methods.